PERAN GURU PAI DALAM MEMBANGUN MORALITAS SISWA PADA ERA DIGITAL DI SMPN 3 TANGERANG SELATAN - Nurul Faridah; Eka Naelia Rahmah (Fakultas Tarbiyah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2025)
This research is motivated by the many impacts caused by the digital era, the development of digital technology has had a significant impact on education, including in building student morality in the digital era. The purpose of this study is to find out how the role of PAI teachers in building student morality in the digital era. This study uses a descriptive qualitative method. The results of the study show that PAI teachers play a very good role in building student morality in the digital era, including: Teachers play the role of educators, teachers play the role of teachers, teachers play the role of supervisors, teachers play the role of advisors, and teachers play the role of models and role models. Of course, the role of the teacher can build morality in the digital era, including: being honest, being yourself, being responsible, independence, moral courage, humility, and critical thinking.